Effect of plasma power on copper substrate used for synthesizing carbon nanotubes via Alcohol Catalytic Chemical Vapor Deposition (ACVD) technique - Phunwaree S. (2017)
© 2016, Chiang Mai Journal of Science. All Rights Reserved. In this work, the authors attempted to modify a plasma treatment on copper substrate to increase its roughness surface by Low Pressure Plasma Treatment (LPPT). Plasma energy at the radio frequency of 13.56 MHz and the mixing gas between 30% Acetylene (C 2 H 2 ) and 70% Hydrogen (H 2 ) were used for treatment condition. Plasma power was varied from 90, 100 and 150 Watt for 20 min, respectively with the gas pressure of 100 mTorr were treated on copper substrate surface. After plasma treatment, treated copper substrate was then used for synthesizing carbon nanotubes via Alcohol Catalytic Chemical Vapor Deposition (ACVD) technique. The samples were then characterized using contact angle, atomic force microscopy (AFM) and scanning electron microscopy (SEM) technique, respectively. From the results, it could be seen that roughness and surface energy of copper substrate was increased with the increasing of plasma power which had affect to higher absorption of Ni catalyst and quantity of obtained nanotubes. Maximum quantity of carbon nanotubes obtained from 100 Watt for 20 min was 41.64% higher than that of non-treat sample. The average diameter of carbon nanotubes was in the range of 30-40 nm.